A template-free method for stable CuO hollow microspheres fabricated from a metal organic framework (HKUST-1). Issue 21 (8th May 2015) - Zhang, Suoying; Liu, Hong; Liu, Pengfei; Yang, Zhuhong; Feng, Xin; Huo, Fengwei; Lu, Xiaohua
Abstract : Uniform CuO hollow microspheres were successfully achieved from a non-uniform metal organic framework by spherical aggregation and Ostwald ripening. Abstract : Uniform CuO hollow microspheres were successfully achieved from a non-uniform metal organic framework by using a template-free method. The process mechanism has been revealed to be spherical aggregation and Ostwald ripening. When tested in CO oxidation and heat treatment, these assembled microspheres exhibited an excellent catalytic performance and show a much better stability than the inherited hollow structure from MOFs.